2013
DOI: 10.1007/s11999-012-2638-3
|View full text |Cite
|
Sign up to set email alerts
|

A Supplemental Video Teaching Tool Enhances Splinting Skills

Abstract: Our observations suggest a supplemental video instructional program improved the performance of musculoskeletal clinical skills in comparison to only a traditional lecture series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…As outcome measures, one study looked at students' selfassessment of clinical abilities, 14 seven studies investigated learners' preparation for clinical procedures, 12,15,16,17,18,19 and two studies focused on students' performance in clinical skills. 20,21 These prospective randomized trials and pilot studies demonstrate that e-learning enhances knowledge acquisition and student satisfaction for preparation and performance in orthopedic skills. Mehrpour et al studied the efficacy of a supplemental video in medical student splinting training.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As outcome measures, one study looked at students' selfassessment of clinical abilities, 14 seven studies investigated learners' preparation for clinical procedures, 12,15,16,17,18,19 and two studies focused on students' performance in clinical skills. 20,21 These prospective randomized trials and pilot studies demonstrate that e-learning enhances knowledge acquisition and student satisfaction for preparation and performance in orthopedic skills. Mehrpour et al studied the efficacy of a supplemental video in medical student splinting training.…”
Section: Resultsmentioning
confidence: 99%
“…Mehrpour et al studied the efficacy of a supplemental video in medical student splinting training. 21 473 medical students were divided into two groups, one received a lecture and the other received a training video to supplement the lecture. An Objective Structured Clinical Examination (OSCE) assessed the competency, knowledge, and skills of the students in thirteen areas of splinting six months after the training.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a similar study was conducted by Mehrpour et al [26] who examined the effect of using a supplemental video teaching tool on enhancing splinting skills between two groups of medical students from three universities hospitals at Tehran and Iran. The study's results revealed that the participants in the educational video group performed substantially better than the students in the traditional teaching group.…”
Section: Discussionmentioning
confidence: 97%